If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -4 = x + -7 Reorder the terms: -4 = -7 + x Solving -4 = -7 + x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1x' to each side of the equation. -4 + -1x = -7 + x + -1x Combine like terms: x + -1x = 0 -4 + -1x = -7 + 0 -4 + -1x = -7 Add '4' to each side of the equation. -4 + 4 + -1x = -7 + 4 Combine like terms: -4 + 4 = 0 0 + -1x = -7 + 4 -1x = -7 + 4 Combine like terms: -7 + 4 = -3 -1x = -3 Divide each side by '-1'. x = 3 Simplifying x = 3
| Y=-16x^2+16x+5 | | Ax+5=bc-c | | x=9x+5-5 | | 6n+4=-2n | | (-32)+x=-18 | | 48kd=3.2k | | 6x-3+x-2=-5 | | X^2+45x-450=0 | | 4x-23/8= | | 12y+y(y-6)=4 | | 9x^2-18-2=0 | | 2(2+2n)=3(n+1) | | -110+3x=33-8x | | 5x+x=-42 | | -8=1/10z+3/10z | | 4x^6-24x^5+8x^4=0 | | 5n+3=2(n+2)+-3n | | y^2-10y-9=0 | | X+2x+3x=440 | | y=2x^2+16x+25 | | -q+9+7q=4q-9 | | 9x-4x+8=1x+20 | | -1/4+6=2/3x+28 | | 5x+2+2-2x=10 | | a=-10 | | y+7=.33333(x+2) | | X-(2x-5)=4x-(x+42) | | [-2x+22-3z]=[6x-2y+45] | | 4=3h-2 | | G-10=-9g+10 | | -2(b+3)=16 | | 3b^2-2b+16=0 |